(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Network (WSN) is the network consists of large number of sensor nodes. These sensor nodes collects large amount of data and transmit it to the base station. But these sensor nodes provide a limited battery power and battery replacement is not an easy method for wireless sensor network. Energy efficient routing protocols provide longer network life time by minimizing total energy consumption and balance the network load. A General Self-Organized Tree-Based Energy-Balance Routing protocol (GSTEB) is the one of the energy efficient routing protocol, which discusses two extreme cases of data fusion that is each sensor node transmits same amount of data and different amount of data. For both cases it builds a routing tree using a process where, for each round, Base Station (BS) assigns a root node and broadcasts this selection to all sensor nodes. Each node selects its parent by considering itself and its neighbor’s information. GSTEB provide an efficient energy balanced routing and longer lifetime for the network, when each sensor node transmits same amount of data or different amount of data. Although GSTEB protocol achieves it has some problems such as difficult to distribute the load evenly on all nodes in tree structure and overhead in the base station. The proposed method (EGSTEB) solves these problems by overhead and energy consumption of sensor nodes.